Application of proper orthogonal decomposition methods in reactive pore diffusion simulations. (17th August 2014) - Ullmann, Martin; Prüfert, Uwe; Seidel, Jens; Ernst, Oliver G.; Hasse, Christian
<x xml:space="preserve">Abstract</x> Reactive pore diffusion is an important process in automotive exhaust‐gas aftertreatment modelling the overall conversion of pollutants. It features highly nonlinear source terms from chemical reactions coupled with transport processes. This work examines the application of model reduction by proper orthogonal decomposition. It is shown that this technique can be successfully applied to the system using separate bases for each species. Using a basis obtained for baseline conditions, predictions can be made for species profiles within a pore system for different conditions, potentially leading to significantly reduced computational requirements.